Pelatihan dan Workshop Badan Usaha Milik Desa (BUMDes) Sebagai Penggerak Ekonomi Masyarakat di Desa Waru Kecamatan Parung Kabupaten Bogor - Ahmad Maulidizen; Risman Nugraha; Abdul Haris Muchtar; Muhammad Hasan Abdul Azis Naibaho; Muhammad Rafi Thoriq; Nuha Afifah Zuhri; Nur Rahmah Zakiyah (MENARA RIAU, 2023)
Badan Usaha Milik Desa (BUMDes) serves as a tool to stimulate rural economic development by harnessing the potential within the village. One of the main obstacles in BUMDes development is the lack of qualified human resources. The objective of this Community Service Program (PKM) is to provide training and workshops to the BUMDes management in Desa Waru, focusing on managerial aspects, developing flagship products, and digital marketing. The method employed in this PKM consists of training and workshops that involve both theoretical instruction and practical application of the provided materials. The participants of this activity are 15 members of the BUMDes management in Desa Waru. The outcome of the PKM is the successful execution of the training and workshop activities for Badan Usaha Milik Desa (BUMDes) as an Economic Driver for the Community in Desa Waru, Parung Subdistrict, Bogor Regency. The materials delivered during this event have met the needs of the participants, who are also BUMDes managers in Desa Waru.